Список предметов

Математика
Литература
Алгебра
Русский язык
Геометрия
Английский язык
Химия
Физика
Биология
Другие предметы
История
Обществознание
География
Українська література
Українська мова
Казак тили
Беларуская мова
Информатика
Экономика
Право
ПОМОГИТЕ ПОЖАЛУЙСТА
СРОЧНО

Решить уравнение

4(х+1)(х+2)(х+3)(х+6)=-3х^2
спросил от в категории Алгебра

1 Ответ

4((x+1)(x+6))*((x+2)(x+3)) = -3x^2
4(x^2 + 7x + 6)*(x^2 + 5x + 6) = -3x^2
Замена x^2 + 6x + 6 = t
4(t + x)(t - x) = -3x^2
4(t^2 - x^2) = -3x^2
4t^2 - 4x^2 + 3x^2 = 0
4t^2 - x^2 = 0
(2t - x)(2t + x) = 0
Обратная замена
(2x^2 + 12x + 12 - x)(2x^2 + 12x + 12 + x) = 0
(2x^2 + 11x + 12)(2x^2 + 13x + 12) = 0
Разложили на 2 квадратных. Решаем их отдельно.

1) 2x^2 + 11x + 12 = 0
D = 11^2 - 4*2*12 = 121 - 96 = 25 = 5^2
x1 = (-11 - 5)/4 = -16/4 = -4
x2 = (-11 + 5)/4 = -6/4 = -1,5

2) 2x^2 + 13x + 12 = 0
D = 13^2 - 4*2*12 = 169 - 96 = 73
x3 = (-13 - √73)/4
x4 = (-13 + √73)/4
ответил от
x
...